Can IS/IT governance contribute for business agility? - Couto, Eduardo Sá (2015)
Business agility is the ability to answer quickly to internal and external changes, either reactively or proactively, in an efficient and effective way. Therefore, it is no surprise that business agility has become one of the top 10 most important organizational concerns for IT management. To achieve business-IT alignment, organizations need to set up processes to support decision making regarding the effective and efficient use of information systems and information technology, i.e., IS/IT Governance. Governance means rules, organizational procedures, supervision, monitoring and control. On the other hand, agility requires degrees of freedom to decide and make changes in the business processes. The possible tension between IS/IT Governance and business agility may be a result of the conflict between adaptation versus anticipation. While governance requires planning, anticipation, supervision and control, agility requires high degrees of adaptation, many times under unforeseen circumstances. In this work, we propose a conceptual model to look into the relationship between IS/IT Governance and business agility.